STUDI KUALITAS BAKTERIOLOGIS AIR KOLAM RENANG DAN FAKTOR – FAKTOR YANG MEMPENGARUHINYA DI KOLAM RENANG KOTA SEMARANG - Shalichah Talita; Nurjazuli Nurjazuli; Hanan Lanang Dangiran (Jurnal Kesehatan Masyarakat (Undip), 2016)
Swimming pool water is water in the pool used for sports and the quality meet health requirements. Based on data from Semarang City Health Office, known in 2013 as many as eight samples of swimming pools water were inspected had total coliforms are not eligible. The purpose of this research is to analyze bacteriological quality of swimming pool and the related factors in Semarang City. The study design of this research was descriptive research with survey method and cross sectional approach. The population study was 11 swimming pools in Semarang City then sample taken by total sampling and the repeated sampling 3 times, so the total sample of this study was 33 samples of swimming pools water. The result showed the number of bacteria and total coliform in Semarang City’s swimming pools 100 % not qualified. Swimming pool with recirculating pools type and using groundwater as raw water as many as 90,9 %. Some 69,7 % of free klorin in the pool water not qualify , while pH values 54,5 % qualified and 72,7 % sanitary conditions pool has also qualified.